2017
DOI: 10.1038/ncb3538
|View full text |Cite
|
Sign up to set email alerts
|

The MBNL3 splicing factor promotes hepatocellular carcinoma by increasing PXN expression through the alternative splicing of lncRNA-PXN-AS1

Abstract: Understanding the roles of splicing factors and splicing events during tumorigenesis would open new avenues for targeted therapies. Here we identify an oncofetal splicing factor, MBNL3, which promotes tumorigenesis and indicates poor prognosis of hepatocellular carcinoma patients. MBNL3 knockdown almost completely abolishes hepatocellular carcinoma tumorigenesis. Transcriptomic analysis revealed that MBNL3 induces lncRNA-PXN-AS1 exon 4 inclusion. The transcript lacking exon 4 binds to coding sequences of PXN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
234
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(237 citation statements)
references
References 58 publications
2
234
0
1
Order By: Relevance
“…Numerous reports have described the intricate interplay between lncRNAs and miRNAs [37]. LncRNA-PXN-AS1 containing exon 4 protects PXN mRNA against degradation induced by the miR-24-Ago2 complex, thereby increasing PXN expression in hepatocellular carcinoma [38]. LINC00673 sponges miR-150-5p and regulates ZEB1 expression indirectly via a competing endogenous RNAs (ceRNA) mechanism in NSCLC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have described the intricate interplay between lncRNAs and miRNAs [37]. LncRNA-PXN-AS1 containing exon 4 protects PXN mRNA against degradation induced by the miR-24-Ago2 complex, thereby increasing PXN expression in hepatocellular carcinoma [38]. LINC00673 sponges miR-150-5p and regulates ZEB1 expression indirectly via a competing endogenous RNAs (ceRNA) mechanism in NSCLC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the precise action mechanisms of lncRNAs remain largely unclear . A mainly proposed action model is that lncRNAs bind to other proteins, DNAs, miRNAs, and/or mRNAs, and further change the expression, location, and/or functions of the interaction partners . In this study, we found that PAX8‐AS1‐N mainly localized in cytoplasm.…”
Section: Discussionmentioning
confidence: 63%
“…The molecular mechanisms mediating the roles of lncRNAs are complex and diverse . As a class of regulatory RNAs, lncRNAs directly bind proteins, DNAs, mRNAs and/or microRNAs . Through interacting with other molecules, lncRNAs regulate the expression, location and/or functions of the interacting partners .…”
Section: Discussionmentioning
confidence: 99%